Towards safer colorectal surgery worldwide: outcomes and benchmarks from the ESCP CORREA 2022 audit - Salmi, Mohamad Irfan; Md Nor, Azmi; Elagili, Faisal; Sainal, Mohd. Yusof (John Wiley and Sons Inc., 2025)
Abstract Introduction: Benchmarking colorectal surgery outcomes informs quality improvement. The ESCP CORREA 2022 snapshot audit aimed to assess contemporary colorectal resection practices and short-term outcomes across European countries and beyond.